IMF Research Bulletin, March 2008. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2008)
IMF research summaries on foreign direct investment (by Yuko Kinoshita) and on trade linkages and business cycles (by Julian di Giovanni and Andrei Levchenko); country study on Mexico (by Roberto Garcia-Saltos); listing of visiting scholars at the IMF during February-June 2008; listing of contents of Vol. 55, Issue No. 1 of IMF Staff Papers; listing of recent IMF Working Papers; and a listing of recent external publications by IMF staff.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet